THE IMPORTANCE OF FINANCIAL EDUCATION IN ELEMENTARY SCHOOL: A PROJECT WITH CHILDREN AND FAMILIES (CIPEEX, 2025)
Financial education is crucial for developing conscious citizens from an early age. This study aims to analyze the effectiveness of educational approaches in raising awareness about financial education among children in the first phase of elementary school, a field with a scarcity of dedicated research. The project employed a qualitative approach, combining a literature review, an online questionnaire for parents (n=56), and an educational intervention workshop for 16 children aged 7 to 10. The intervention used playful and interactive strategies, such as storytelling with Monica's Gang characters, theater, and a simulated "ambulant market." The questionnaire results revealed that while 94.6% of parents recognize the importance of early financial education, 54.4% of children do not receive a regular allowance. However, most families share financial information (58.9%) and encourage the habit of saving (76.8%). The practical workshop was highly successful, with participant reports confirming the effectiveness of the engaging methodology. The study concludes that introducing financial education through ludic activities is an effective strategy for developing financial literacy from childhood, forming individuals capable of making informed and responsible financial decisions. This project highlights the potential of such initiatives to positively contribute to children's future financial development.
Keywords: Financial Education; Children; Elementary School; Playful Learning